ANALISIS PERSEPSI MASYARAKAT TERHADAP PENTINGNYA PENDIDIKAN TINGGI BAGI KAUM PEREMPUAN DI DESA BAIPAJUNG TANAH MERAH BANGKALAN - zubaida; Dian Eka Indriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education is a conscious effort to pass on culture from one generation to the next. However, there is still a negative view of higher education for women, which is based on the general perception that